2019
DOI: 10.1002/ajmg.a.61133
|View full text |Cite
|
Sign up to set email alerts
|

Biallelic novel missense HHAT variant causes syndromic microcephaly and cerebellar‐vermis hypoplasia

Abstract: We report two siblings with microcephaly, early infantile onset seizures, and cerebellar vermis hypoplasia, in whom whole exome sequencing revealed a novel homozygous missense (c.770T>C, p.[Leu257Pro]) variant in the hedgehog acyl‐transferase gene (HHAT), encoding an enzyme required for the attachment of palmitoyl residues that are critical for multimerization and long and short range hedgehog signaling. There is a report of one family with Nivelon–Nivelon–Mabille syndrome in which HHAT was proposed as the lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
23
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 15 publications
4
23
2
Order By: Relevance
“…The overlapping phenotypes in the previous two families and the present family include microcephaly, short stature, elevated creatinine phosphokinase levels, and skeletal dysplasia. Small cerebellar vermis was reported in the previous two families ( Abdel-Salam et al, 2019;Callier et al, 2014). Alobar holoprosencephaly and a single median central incisor are reported only in the present family, and no other signs of holoprosencephaly were noted previously in individuals with variants in HHAT.…”
Section: Clinical Reportsupporting
confidence: 45%
See 1 more Smart Citation
“…The overlapping phenotypes in the previous two families and the present family include microcephaly, short stature, elevated creatinine phosphokinase levels, and skeletal dysplasia. Small cerebellar vermis was reported in the previous two families ( Abdel-Salam et al, 2019;Callier et al, 2014). Alobar holoprosencephaly and a single median central incisor are reported only in the present family, and no other signs of holoprosencephaly were noted previously in individuals with variants in HHAT.…”
Section: Clinical Reportsupporting
confidence: 45%
“…Subsequently, Abdel-Salam et al described a second family with two affected female siblings with microcephaly, small cerebellar vermis, seizures, and skeletal dysplasia. In this family, they identified a biallelic missense variant, c.770C>T, p.(Leu257Pro), in exon 7 of HHAT (NM_001122834.3) as the likely cause of the multiple malformation syndrome (Abdel-Salam et al, 2019). The Leu257 residue also lies in the MBOAT domain.…”
mentioning
confidence: 98%
“…HHAT is a hedgehog acyltransferase, required for the post‐translational palmitoylation of Hedgehog proteins. Abdel‐Salam et al 21 reported a biallelic novel missense HHAT variant that might cause syndromic microcephaly and cerebellar‐vermis hypoplasia. HHAT mutations can also be indicative of severe acrania‐holoprosencephaly‐agnathia craniofacial defects.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, bi-allelic loss-of-function variations in SMO or Hedgehog acyl-transferase (HHAT) genes in humans led to many developmental anomalies including microcephaly 56,57 . While it is unknown whether microcephaly in humans caused by inactivating mutations in NDE1 is due to abnormally long cilia and/or reduced Hedgehog activity (GLI2), our data lend support to this idea.…”
Section: Discussionmentioning
confidence: 99%